2015
DOI: 10.1155/2015/179126
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Preview Controller for Discrete-Time Systems Based on LMI

Abstract: A preview controller design method for discrete-time systems based on LMI is proposed. First, we use the difference between a system state and its steady-state value, instead of the usual difference between system states, to transform the tracking problem into a regulator problem. Then, based on the Lyapunov stability theory and linear matrix inequality (LMI) approach, the preview controller ensuring asymptotic stability of the closed-loop system for the derived augmented error system is found. And an extended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Therefore, it is obvious that if one can design a guaranteed cost static output feedback controller (33) to robustly stabilize the augmented system (27), then the preview repetitive controller (7) can also stabilize the original system (1) and such that lim k→∞ e(k) = 0.…”
Section: Design Of Guaranteed-cost Preview Repetitive Controllermentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is obvious that if one can design a guaranteed cost static output feedback controller (33) to robustly stabilize the augmented system (27), then the preview repetitive controller (7) can also stabilize the original system (1) and such that lim k→∞ e(k) = 0.…”
Section: Design Of Guaranteed-cost Preview Repetitive Controllermentioning
confidence: 99%
“…In the following, we will give the sufficient conditions for the existence of a guaranteed cost static output feedback controller (33) to robustly stabilize the augmented system (27).…”
Section: Design Of Guaranteed-cost Preview Repetitive Controllermentioning
confidence: 99%
See 1 more Smart Citation
“…The future values of the reference signal are assumed not to change beyond the k+MR, namely, r)(k+j=r)(k+MR,j=MR+1,MR+2,MR+3,. Remark 2 A2 is the assumption that the reference signal is previewable. Theoretical research and practical examples have shown that the previewable signal has impacted performance of the control system significantly only for a certain time period, during which the reference signal exceeds the preview length impact is small; therefore, the reference signal is assumed to be some constant when it exceeds the preview length [37]. In fact, a regular feedback control system does not take full advantage of the known future values, or equivalently, MR=0.…”
Section: Problem Formulation and Basic Assumptionsmentioning
confidence: 99%
“…In order to reflect the uncertainty, the uncertain parameters a i ( i = 1 , 2 , 3 , 4 , 5), with absolute values no more than 0.5, are taken as random numbers. Note that if the selecting method for the auxiliary variables truex¯(),k and trueu¯(),k in is adopted, then the initial conditions should be decided based on different situations. The proposed method can avoid the limitation on initial conditions.…”
Section: Numerical Examplementioning
confidence: 99%